Using structural neuroanatomy to identify trauma survivors with and without post-traumatic stress disorder at the individual level. Issue 1 (3rd April 2013) - Gong, Q.; Li, L.; Tognin, S.; Wu, Q.; Pettersson-Yeo, W.; Lui, S.; Huang, X.; Marquand, A. F.; Mechelli, A.
Abstract : Background: At present there are no objective, biological markers that can be used to reliably identify individuals with post-traumatic stress disorder (PTSD). This study assessed the diagnostic potential of structural magnetic resonance imaging (sMRI) for identifying trauma-exposed individuals with and without PTSD. Method: sMRI scans were acquired from 50 survivors of the Sichuan earthquake of 2008 who had developed PTSD, 50 survivors who had not developed PTSD and 40 healthy controls who had not been exposed to the earthquake. Support vector machine (SVM), a multivariate pattern recognition technique, was used to develop an algorithm that distinguished between the three groups at an individual level. The accuracy of the algorithm and its statistical significance were estimated using leave-one-out cross-validation and permutation testing. Results: When survivors with PTSD were compared against healthy controls, both grey and white matter allowed discrimination with an accuracy of 91% ( p < 0.001). When survivors without PTSD were compared against healthy controls, the two groups could be discriminated with accuracies of 76% ( p < 0.001) and 85% ( p < 0.001) based on grey and white matter, respectively. Finally, when survivors with and without PTSD were compared directly, grey matter allowed discrimination with an accuracy of 67% ( p < 0.001); in contrast the two groups could not be distinguished based on white matter. Conclusions: These results reveal patterns of neuroanatomical alterations that could be used to inform the identification of trauma survivors with and without PTSD at the individual level, and provide preliminary support to the development of SVM as a clinically useful diagnostic aid.